Design of ultrahigh-affinity and dual-specificity peptide antagonists of MDM2 and MDMX for P53 activation and tumor suppression - Xiang Li; Neelakshi Gohain; Si Chen; Yinghua Li; Xiaoyuan Zhao; Bo Li; William D. Tolbert; Wangxiao He; Marzena Pazgier; Honggang Hu; Wuyuan Lu (Elsevier, 2021)
Peptide inhibition of the interactions of the tumor suppressor protein P53 with its negative regulators MDM2 and MDMX activates P53 in vitro and in vivo, representing a viable therapeutic strategy for cancer treatment. Using phage display techniques, we previously identified a potent peptide activator of P53, termed PMI (TSFAEYWNLLSP), with binding affinities for both MDM2 and MDMX in the low nanomolar concentration range. Here we report an ultrahigh affinity, dual-specificity peptide antagonist of MDM2 and MDMX obtained through systematic mutational analysis and additivity-based molecular design. Functional assays of over 100 peptide analogs of PMI using surface plasmon resonance and fluorescence polarization techniques yielded a dodecameric peptide termed PMI-M3 (LTFLEYWAQLMQ) that bound to MDM2 and MDMX with Kd values in the low picomolar concentration range as verified by isothermal titration calorimetry. Co-crystal structures of MDM2 and of MDMX in complex with PMI-M3 were solved at 1.65 and 3.0 Å resolution, respectively. Similar to PMI, PMI-M3 occupied the P53-binding pocket of MDM2/MDMX, which was dominated energetically by intermolecular interactions involving Phe3, Tyr6, Trp7, and Leu10. Notable differences in binding between PMI-M3 and PMI were observed at other positions such as Leu4 and Met11 with MDM2, and Leu1 and Met11 with MDMX, collectively contributing to a significantly enhanced binding affinity of PMI-M3 for both proteins. By adding lysine residues to both ends of PMI and PMI-M3 to improve their cellular uptake, we obtained modified peptides termed PMI-2K (KTSFAEYWNLLSPK) and M3-2K (KLTFLEYWAQLMQK). Compared with PMI-2K, M3-2K exhibited significantly improved antitumor activities in vitro and in vivo in a P53-dependent manner. This super-strong peptide inhibitor of the P53-MDM2/MDMX interactions may become, in its own right, a powerful lead compound for anticancer drug development, and can aid molecular design of other classes of P53 activators as well for anticancer therapy.